THE EARLY KURGAN PERIOD IN RABATI, GEORGIA: THE CULTURAL SEQUENCE AND A NEW SUITE OF RADIOCARBON DATES. Issue 6 (22nd December 2021) - Bedianashvili, Giorgi; Jamieson, Andrew; Sagona, Claudia
Abstract: This paper reports on radiocarbon ( 14 C) results from the recent archaeological investigations in the ancient frontier fortress of Rabati, in southwest Georgia, a collaborative research project involving archaeologists from the Georgian National Museum and the University of Melbourne. From the first three excavation seasons spanning 2016, 2018, and 2019, it became clear that significant Bedeni phase deposits capped most of the summit of the site. Levels with their distinctive vessels and a range of contemporary, local domestic wares, pits and some traces of architecture seal underlying Early Bronze Age strata. The Early Bronze Age levels include massive architecture rarely seen in Kura-Araxes settlements. Some finds can only be described as unique and extraordinary while others suggest that the core population was stable with long-held traditions, yet open to new influences infiltrating this highland site during the subsequent Early Kurgan (Martkopi-Bedeni) period. We discuss the key discoveries at Rabati relative to the 14 C readings from the site within the wider setting of contemporary sites in the Caucasus.